The Application of Mixed Reality Technology in The 5.0 Era Learning Pencak Silat to Support The Independent Curriculum - Mohamad Dai; Rohmad Apriyanto; Ishimoto Kaito; Choiriya Dwi Yusrowatin; Suningsih Suningsih (Journal of Sport Science and Education, 2024)
Pencak silat, as a cultural heritage and traditional sport of Indonesia, holds high cultural, spiritual, and physical skill values. One of the promising technologies in the 5.0 era to be applied in supporting the Independent Curriculum is Mixed Reality (MR). This research aims to develop and test the application of MR technology in the learning of pencak silat to support the Independent Curriculum in the 5.0 era. Using the Research and Development (R&D) method, this study goes through several stages, including needs analysis, product development, product design, development, implementation, and finally evaluation. The developed MR application allows students to learn the movements of pencak silat virtually in an interactive environment. The research results indicate a significant improvement in students' abilities. The average pretest score of 60.35 increased to 85.45 on the posttest after the use of the MR application, demonstrating an enhancement in students' understanding and skills. In addition, the results of the validation tests by material and media experts are both in the "Very Good" category, indicating that this MR application is suitable for use in learning. This technology also supports more flexible learning in accordance with the principles of the Independent Curriculum, which emphasizes differentiated learning, although there are challenges regarding infrastructure readiness and teacher training.